National Policy for Internationalisation in Higher Education: The Case of Mozambique - Ndaipa, Charnaldo; Edström, Kristina; Geschwind, Lars (Nordic Journal of Comparative and International Education (NJCIE), 2022)
The impetus of this study is to explore the internationalisation of higher education policy in Mozambique at a national level. Internationalisation has been one of the major themes of discussion across countries but except for South Africa, it is rarely researched in sub-Saharan Africa from the perspective of the policy of higher education at a national level. This study is qualitative and applies the policy analysis method. Data derive from higher education policy documents and semi-structured interviews with policy-makers. Two research questions are asked. First, how do policy-makers understand and strategise the internationalisation of higher education in Mozambique? Second, what are the rationales and challenges for undertaking internationalisation of higher education? The findings reveal that internationalisation is understood as mobility of students and staff, establishment of agreements and cooperation and integration of higher education in the Southern African Development Community and worldwide. The findings further reveal that the rationales for undertaking internationalisation of higher education policy encompass quality, academic training, competitiveness, prestige, and knowledge production. An ideological mismatch in the strategies of the internationalisation between policy-makers and policy documents was noted, identifying opportunities for a more creative approach.